2022
DOI: 10.1177/19418744211067353
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Amyloid Angiopathy and Atrial Fibrillation: An up to Date Case Report

Abstract: Concurrent Cerebral Amyloid Angiopathy (CAA) and Atrial Fibrillation are becoming an increasingly common dilemma in clinical practice due to the aging population and the comorbidities associated with it. In such patients, the physician must appreciate and strike the difficult balance between the risk of ischemic strokes from atrial fibrillation on one hand, and that of intracerebral hemorrhage from coexisting CAA on the other. Anticoagulation is necessary for the former but potentially deleterious for the latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Hemorrhagic and ischemic manifestations occur frequently in CAA and cause management dilemmas. 3 , 4 A presenting feature of CAA may be a TFNE, which may be difficult to distinguish from TIAs. CAA‐related TFNEs can be an initial sign for a high risk of future ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhagic and ischemic manifestations occur frequently in CAA and cause management dilemmas. 3 , 4 A presenting feature of CAA may be a TFNE, which may be difficult to distinguish from TIAs. CAA‐related TFNEs can be an initial sign for a high risk of future ICH.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic risk is often reduced by anticoagulants. However, patients with CAA have a high risk of intracerebral hemorrhage (ICH), worsened by anticoagulation therapy[ 1 - 3 ]. This clinical dilemma is increasingly becoming a common scenario, due to the aging of the population.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to ICH, CAA can also cause ischemic events such as microinfarcts. Other important clinical manifestations of CAA may include cognitive impairments, transient neurological symptoms, and inflammatory leukoencephalopathy[ 1 , 2 ]. This clinical and pathological heterogeneity could indicate related but distinct phenotypes of CAA, reflected in different clinical syndromes[ 2 - 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels affected by CAA are predisposed to rupture, which is a major cause of spontaneous and frequently recurrent lobar cerebral hemorrhage 1 . Prevention of stroke or arterial embolism in patients with cerebral amyloid CAA, intracerebral hemorrhage (ICH) and atrial fibrillation (AF) is a therapeutic dilemma 2 . Both antiplatelet drugs (AP) and anticoagulants (AC) increase the risk of recurrent ICH, why left atrial appendage closure (LAAC) is suggested (Table 1).…”
Section: Introductionmentioning
confidence: 99%